Reflective Maternal Method Implementation in Improving Vocabulary Knowledge of Deaf Children in Class 1 of SLB-B Sumbersari Bandung - Karyana, Shintiya Erni; Rusyani, Endang; Setiawan, Atang (International Conference on Elementary Education, 2021)
The study was conducted on subjects of deaf children in class 1 of SLB-B Sumbersari Bandung. As a result of their deafness, deaf children are limited in language and communication and have low vocabulary knowledge. Therefore, this study aimed to discover the reflective maternal method implementation in improving deaf children's vocabulary knowledge. This method stimulates deaf children to optimize their abilities in knowing vocabularies, i.e., nouns by conducting conversations, visualizations, word deposits, and reflections. Based on the problems, it is necessary to provide special treatments to improve vocabulary knowledge, especially on object uses. The method used in this study was the Single-Subject Research (SSR) experiment by a quantitative approach by using the A-B-A design. The data collection technique used was three test types, i.e., verbal test, action test, and written test. This study was carried out on two deaf children. Study findings based on baseline 1 and baseline 2 scores show that the baseline 2 result was higher and had a score increase post-intervention. It is proven by the two subjects who managed to mention object names, showing object names, and matching object names and object uses. The reflective maternal method is a method by the active learning process that triggers children to conduct a natural conversation, as they occur between mother and child. This study can be implemented as a recommendation for associated teachers in their learning method, particularly in using the reflective maternal method to improve object or other material vocabulary knowledge on deaf children.